Comparative analysis of antioxidant activities of essential oils and extracts of fennel (Foeniculum vulgare Mill.) seeds from Egypt and China - Adel F. Ahmed; Mengjin Shi; Cunyu Liu; Wenyi Kang (Food Science and Human Wellness)
The present study was conducted to assay the antioxidant activities of essential oils and ethanol extracts of fennel (Foeniculum vulgare Mill.) seeds from Egypt and China. The major components of the Egyptian fennel essential oil were estragole (51.04%), limonene (11.45%), l-fenchone (8.19%) and trans-anethole (3.62%) by GC–MS analysis. Whereas, the major constituents of Chinese fennel essential oil were trans-anethole (54.26%), estragole (20.25%), l-fenchone (7.36%) and limonene (2.41%). The fennel seed extracts from Egypt and China contained appreciable levels of total phenolic contents (42.24 and 30.94 mg PE/g, respectively). The extracts exhibited good DPPH radical scavenging capacity with IC50 (6.34 and 7.17 mg/g), respectively. A high variation in free radical scavenging activities of essential oils was observed. The Chinese fennel essential oil showed high activity in DPPH radical scavenging with IC50 (15.66 mg/g). The Egyptian fennel essential oil showed very low activity with IC50 (141.82 mg/g). The results of the present investigation demonstrated significant variations in the antioxidant activities of fennel essential oils and extracts from Egypt and China. Keywords: Foeniculum vulgare, Essential oils, GC–MS, Total phenolic contents, Antioxidant activities